The effect of fuel prices and sea wave height on mackarel tuna prices in Banda Aceh: A case study at the Ocean Fisheries Port (PPS) Kutaraja, Lampulo District, Banda Aceh City - Aufa, Safarul; Yuliana, Ernik; Harijati, Sri (Universitas Malikussaleh, 2025)
This study aims to analyze the influence of fuel prices (BBM) and sea wave height on the price of mackarel tuna in Banda Aceh City, with a case study at the Ocean Fisheries Port (PPS) Kutaraja Lampulo. The study uses monthly secondary data from 2019 to 2024 and applies a Linear Regression Model for analysis. The regression results indicate that both fuel prices and sea wave height have a significant effect on mackarel tuna prices at the 0.05 significance level. The wave height variable shows a positive coefficient, indicating that higher waves tend to increase mackarel tuna prices. This finding is consistent with the theory that extreme sea conditions hinder fishing activities, reduce fish supply, and consequently increase prices. However, the fuel price variable shows a negative coefficient, contrary to the economic theory that rising fuel prices should increase commodity prices due to higher production costs. This result is likely due to the stability of fuel prices (diesel fuel) during the observation period and the operational efficiency achieved through the use of technology by fishermen, allowing them to maintain or even improve catch volumes despite rising fuel prices. Keywords: Fuel Price; Mackarel Tuna Price; Wave Height